ANALISIS FAKTORâFAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR GO PUBLIC (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Lydia Kartika Trisnawati, 0635030705; Badjuri, Achmad (Students Journal of Accounting and Banking, 2015)
This study aims to analize the influence between the asset structure, profitability, firm size, liquidity and business risks to capital structure of manufacture companies which listed in Indonesian Stock Exchange. This study uses a quantitative method, with secondary data obtained from the Indonesia Stock Exchange and the Indonesian Capital Market Directory. Samples were selected by purposive sampling and obtained 89 samples of manufacture companies listed in 2011-2013. Methods of data analysis was done by using multiple regression test to determine the effect of asset structure, profitability, company size, liquidity and business risks to capital structure.Results of this study stated that the size of the firms have a significant positive effect on the capital structure, profitability and liquidity have a significant negative effect on the capital structure, while the structure of the assets and business risks do not affect the capital structure.Keywords: Asset Structure, Profitability, Company Size, Liquidity, Business Risks, Capital Structure